Perbaikan Sistem Kerja untuk Meningkatkan Keselamatan dan Kesehatan Kerja (K3) Serta Produktivitas Melalui Pendekatan Ergonomi Partisipatif (Studi Kasus Di PT. Eka Karya Sinergi Bandung) - Mochamad Riyan; Paulus Sukapto; Thedy Yogasara (Universitas Katolik Parahyangan, 2023)
The needs of employees in their work are driven by the need for a safe, comfortable, and peaceful work environment to achieve maximum productivity. Productivity in the production activities at the PT. Eka Karya Sinergi production unit, which mainly produces lightweight steel products, is not yet optimal. Several factors can affect the productivity of workers at PT. Eka Karya Sinergi, including a less structured work system, ranging from occupational health and safety levels, work management, worker fatigue levels during the work processes, and complaints experienced by the workers. This research aims to improve the work system to enhance occupational health and safety as well as company productivity through a participatory ergonomics approach. The method used in this research is a qualitative descriptive approach. The occupational health and safety conditions were measured using two instruments, namely REBA and GOTRAK. The participatory ergonomics process was carried out through discussions using Focus Group Discussions. The results of the research show that through the improvement of the work system using the participatory ergonomics method, ergonomic hazards that were previously categorized as high-risk have been reduced to a safer category. This is evidenced by the process of assembling finished goods through the provision of new chairs, which resulted in a risk reduction of 12 points in the SNI 9011 score and 7 points in the REBA score. Furthermore, the improvement of work posture in the process of pumping handling coils with a handstaker resulted in a risk reduction of 4 points in the SNI 9011 score and 5 points in the REBA score. Additionally, the addition of a helper in the process of handling coil materials to the uncoiler machine can reduce the risk by 3 points in the SNI 9011 score and 5 points in the REBA score.